Odpowiedzi

2010-03-21T16:09:14+01:00
O,5X - O,75(X-4x+1)=1-x+1/4
0,5x-2,25x+0,75=1-x+0,2
-1,75x=-0,25-x+0,2
-0,75x=-0,05
x=0,0(66)
2010-03-21T16:24:53+01:00
0.5x - 0.75(x-(4x+1)) = 1 - x + 1/4
0.5x - 0.75(x-4x-1) = 1-x+1/4
0.5x - 0.75x +3x - 0.75 = 1-x+1/4
2.75x - 0.75x = 1-x+1/4
3.75x=2 /: 3,75
x= o,5(3)
6 1 6
  • kufc
  • Początkujący
2010-03-21T16:52:24+01:00
0.5x-0.75(x-(4x+1))=1-x+1/4
0.5x-0.75(x-4-1)=1-x+0,25
0.5x-0.75x+3+0.75=1.25-x
0.5x-0.75x+x=1.25-3-0.75
0.75x=-2.5 /:0.75
x= -3 1/3
(-3,3333...)